2022
DOI: 10.1093/asj/sjac085
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of a Microneedling Device for Treating Wrinkles on the Neck

Abstract: Background A microneedling pen has been cleared by the US Food and Drug Administration and is indicated for improving the appearance of facial acne scars in adults. Objectives The objective of this study was to assess the effectiveness of this microneedling pen for treating wrinkles. This paper focusses on the results on the neck, an area of recent importance with video meetings placing physical stress on the neck area leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Skin remodeling via the use of transdermal microneedling procedures has been shown to reduce fine lines and wrinkles, improve skin texture, and improve the appearance of dermatological imperfections such as acne scars, surgical scars, cellulite, and stretch marks 24 . This study expands the utility of microneedling into a potential treatment modality for acne.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Skin remodeling via the use of transdermal microneedling procedures has been shown to reduce fine lines and wrinkles, improve skin texture, and improve the appearance of dermatological imperfections such as acne scars, surgical scars, cellulite, and stretch marks 24 . This study expands the utility of microneedling into a potential treatment modality for acne.…”
Section: Discussionmentioning
confidence: 69%
“…The efficacy of treating acne scars and wrinkles has previously been established, and other possible clinical applications for microneedling are being investigated. 24 Currently, microneedling is contraindicated for treating acne vulgaris in some regions, one being the United States. It is a general perception in the medical community that microneedling over inflammatory acne lesions can act to exacerbate acne via the spreading of C. acnes bacterium from acneic lesions to other areas of the face.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on micro-needling from the literature focus mainly on face skin [ 7 , 8 , 9 , 10 , 11 ] and there are still very few that discuss its effect on the neck and cleavage [ 12 , 13 ]. Furthermore, micro-needling is often used in combination with other treatments, which makes an assessment of its efficacy and safety more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant literature reports, DMN is often used as a carrier for drug delivery such as insulin, 5-aminolevulinic acid, low molecular weight heparin, ovalbumin, adenovirus vector, a variety of vaccine antigens, and biomolecular molecules (22). It has been used in the treatment of skin diseases (23)(24)(25), metabolic diseases (26, 27), immune diseases (2, 28), and medical cosmetology (29, 30). The results of this study showed that the construction of soluble microneedles based on AM-ae has a good therapeutic effect on the treatment of breast hyperplasia.…”
mentioning
confidence: 99%